2019
DOI: 10.1007/s10616-018-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitronectin, fibronectin and epidermal growth factor induce proliferation via the JNK and ERK pathways in insulinoma INS-1 cells

Abstract: An insulinoma is a tumor formed by beta cells in the Langerhans islets of the pancreas. Vitronectin (VTN), fibronectin (FN) and epidermal growth factor (EGF) are important in cell signaling. The aim of this study was to investigate the molecular mechanism that occurs in INS-1 cells with the administration of VTN, FN and EGF in proliferative doses. We determined the proliferative doses of EGF, VTN and FN. The molecular mechanism of proliferation has been investigated alone or in the combination of these protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Studies showed that both the insulin and NGF immunofluorescent labelling was weaker in insulinoma samples (Vidaltamayo et al 2003). Epidermal growth factor (EGF) appears in pancreatic ductal adenocarcinomas, and an in vitro study showed increase in level of JNK after administration of EGF, vitronectin and fibronectin in insulinoma cells (Kacar and Bolkent 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that both the insulin and NGF immunofluorescent labelling was weaker in insulinoma samples (Vidaltamayo et al 2003). Epidermal growth factor (EGF) appears in pancreatic ductal adenocarcinomas, and an in vitro study showed increase in level of JNK after administration of EGF, vitronectin and fibronectin in insulinoma cells (Kacar and Bolkent 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Parallel to other MAPKs, the JNK pathway is important for proliferation. Phosphorylation of JNK contributes to proliferation of lung adenocarcinoma cells, potentiates hepatocellular carcinoma and colorectal cancer progression and metastases (Xiao et al., 2016; Chan et al., 2017; Karatug Kacar et al., 2019; Cao et al., 2020). Furthermore, activation of JNK was related with increased proliferation and growth of human pancreatic cancer (Choi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the JNK pathway plays a pivotal role in cell proliferation. JNK is phosphorylated in lung adenocarcinoma cells, hepatocellular carcinoma, colorectal cancer and pancreatic cancer, where it contributes to the progression of malignant cells and metastases [ 57 , 58 , 59 , 60 , 61 ]. Moreover, JNK phosphorylation is increased in PSCs subjected to hypoxia, and its inhibition is related to a decrease in cell viability [ 6 ].…”
Section: Discussionmentioning
confidence: 99%